The Implicatures Used in the Debate Between Barrack Obama and John McCain - Aqromi, Nur Lailatul (LP2M Institut Teknologi dan Bisnis ASIA Malang, 2011)
This study focuses on the utterances through debate using Grice’s theory of implicature. Implicature is part of pragmatics study that concerns with implied meaning that is inferred from an utterance or words, but it is not the truth of utterance or words. Besides, in political debate when two people of different political persuasions confront each other, there is more at stake than grasping the immediate meaning of the words they use, moreover they also practicing language game which contain a lot of implicatures. Based on this background, the study about the implicature is intended to describe kinds of implicatures found in the debate between Barack Obama and John McCain and how the implicatures are used in the debate between Barack Obama and John McCain. The data are taken in the forms of conversations done by Barrack Obama and John McCain in their first debate which is held by Missisipi University on September 26th 2008. The result of this study reveals some findings covering the formulated research problems. Finally, the writer suggests to the next researcher analyzes conversational implicature not only focuses on the type but also the characteristics of the conversational implicature in order to attain deep analysis toward Implicature’s theory.